Rwanda’s success in advancing midwifery education: a blueprint of a sustainable, nationally driven curriculum standardization - Malin Bogren; Menelas Nkeshimana; Innocent Nzabahimana; Frida Temple; Marie Claire Iryanyawera; Jean de Dieu Uwimana; Renata Tallarico; Olugbemiga Adelakin; Kerstin Erlandsson (Global Health Action)
The International Confederation of Midwives (ICM) defines and sets the Essential Competencies for Midwifery Practice and provides a framework for developing and reviewing midwifery curricula. This framework ensures that pre-service midwifery education designed for students leads to the demonstration of the required midwifery specific competencies. The development of the ICM competencies in 2024 confirms the timeliness of the effort of Rwanda to update its national curricula. This commentary showcases the blueprint followed by Rwanda to standardize and culturally adapt its midwifery curricula at diploma, bachelor and master’s level to be competency-based and aligned with ICM. National ownership played a pivotal role in the standardization process, as the direction, priorities, and implementation of the curricula review initiative were driven by the country’s own government, higher learning institutes, national midwifery association and other national organizations. Rwanda’s experience in aligning its national curricula with international standards could serve as a model for south–south cooperation.